2023
DOI: 10.1021/acs.macromol.3c00872
|View full text |Cite
|
Sign up to set email alerts
|

Circular Polyolefins: Advances toward a Sustainable Future

Abstract: Plastics offer several advantages, but their production and disposal processes have severe environmental implications. To overcome these issues, there is a need to switch from the linear to a circular economy by recycling plastic waste and by utilizing renewable resources to create bioplastics. However, this is challenging in the case of nonbiodegradable polyolefins (POs), which form the largest fraction of produced polymers and the least recycled one. Mechanical recycling, chemical recycling, and PO bioplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 146 publications
(369 reference statements)
0
6
0
Order By: Relevance
“…Though very nascent at the research stage, such vitrimers surely have potential for reversible crosslinks if careful consideration of a balance between solid-like mechanical properties and true recyclability can be achieved. Yet another interesting review was presented by Moghaddam et al [44], who suggested that such sustainable circular polyolefin efforts were mostly a consequence of global warming and the ubiquitous microplastic challenge looming over the polymer industry [45][46][47]. This research team also emphasized the bio-propane and other olefinbased synthesis (Bio-PP) approach as a stepping stone for TPO to maintain its supremacy in the changing market.…”
Section: Sustainability Aspectmentioning
confidence: 99%
“…Though very nascent at the research stage, such vitrimers surely have potential for reversible crosslinks if careful consideration of a balance between solid-like mechanical properties and true recyclability can be achieved. Yet another interesting review was presented by Moghaddam et al [44], who suggested that such sustainable circular polyolefin efforts were mostly a consequence of global warming and the ubiquitous microplastic challenge looming over the polymer industry [45][46][47]. This research team also emphasized the bio-propane and other olefinbased synthesis (Bio-PP) approach as a stepping stone for TPO to maintain its supremacy in the changing market.…”
Section: Sustainability Aspectmentioning
confidence: 99%
“…However, mass production of polyolefin materials has caused considerable energy crisis, and rapid accumulation of polymer waste has posed serious environmental pollution . Although incineration and thermal energy utilization seems to be a successful industrialized method for polyolefin “recycling”, , high energy consumption and waste gas emission makes this technique deviate from the principle of sustainability. Very recently, conversion of polyolefin wastes into value-added chemicals has become an increasingly appealing research field, , but it is still miles away to achieve practical application of these advanced technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving sustainable polymeric materials is becoming increasingly important for social, scientific, and economic development. It is intuitive that different polymer wastes could be mechanically mixed to satisfy the demand of creating novel materials and achieving sustainability. However, most polymers, even those with similar chemical structures, are thermodynamically immiscible due to small changes in entropy during the mixing process. , As a result, polymer blends usually tend to have large phase-separated domains and consequently low mechanical performance. The use of compatibilizers such as suitable block copolymers is a well-established approach to enhance the performance of immiscible and partially miscible blends, transforming the coarse morphology of the immiscible blend into fine morphology by reducing the interfacial tension. The compatibilization efficiency of block copolymers of varying molecular weight and mass concentration in immiscible polymer blends has been intensively investigated. A general conclusion from these works is that there exists an optimal molecular weight and mass concentration of copolymers to achieve their best compatibilization efficiency.…”
Section: Introductionmentioning
confidence: 99%